"Bill is now singing": Joint engagement and the emergence of social communication of three young children with autism. (January 2015) - Vaiouli, Potheini; Grimmet, Kharon; Ruich, Lawrence J
Young children with autism spectrum disorder meet significant challenges in joint attention skills and in social communication. A child-centered, improvisational, music therapy intervention model was implemented to promote engagement in three young children with autism in a kindergarten classroom. A multiple baseline design compared the children's performance through three phases of intervention: focus on faces, response to joint attention, and initiation of joint attention. A complimentary qualitative analysis of teacher and parent experiences allowed for an in-depth understanding of the role of social environment in supporting emerging social communication skills among three children. As all children showed improvement in joint attention and actions of social engagement, this study bears evidence on the potential of music therapy as a promising intervention for promoting social skills of young children with autism spectrum disorder.